Classification of queueing models for a workstation with interruptions : a review - Wu, Kan (2014)
Queueing theory is commonly used to evaluate the performance of production systems. Due to the complexity of practical production lines, choosing correct queueing models under the existence of interruptions can be intricate, but is critical to the evaluation of system performance. This paper give a review of research in this area, proposes a systematic way to classify different types of interruptions in manufacturing systems and suggests proper queueing models for each category. The operational definition of service time is given and the decomposition properties for the run-based 10 state-induced and time-based pre-emptive events are explained. The corresponding G/G/1 approximate models are proposed.